DETERMINAN KINERJA PEGAWAI DINAS KEBUDAYAAN KABUPATEN GIANYAR - I Dewa Agung Ayu Eka Idayanti; Gusti Agung Ayu Prabandari; Gusti Komang Suryani (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2023)
Researchers have developed various factors, such as job dedication, motivation, and discipline, that affect employee performance. Work motivation, commitment, and discipline are a few factors that can impact employee success in the Gianyar Regency Cultural Office. This study attempts to determine if staff performance at the Cultural Office of the Gianyar Regency is significantly impacted both simultaneously and in part by job motivation, dedication, and discipline. This study includes a proportionate random sample of 58 staff members from the Gianyar Regency's Cultural Office. The findings demonstrate how employee performance is influenced by job motivation, dedication, and discipline.